Pelaksanaan Pembiayaan Mudarabah dan Musyarakah Syirkatul Milk di Bank Muamalat - Zulkifli Zainuddin (INSTITUT PEMBINA ROHANI ISLAM JAKARTA, 2022)
This study is to analyze the focus of the problem on the application of operational principles, implementation of basic concepts, and legal construction in the contract/mudharabah financing contract and musharakah syirkatul milk in the sharia banking system. So that it can be seen whether the application of the two contracts above is applied in accordance with its provisions. This study uses qualitative methods with normative and empirical juridical research types and is descriptive in nature which describes the applicable laws and regulations which are then linked to legal theories in the implementation of mudharabah and musyarakah syirkatul milk financing. The results of the research are from (1) The application of the operating principle of profit sharing in mudharabah financing refers to the agreement between the Bank as shahibul maal and the manager (mudharib) while Musyarakah syirkatul milk financing, namely the bank unionizes with the customer/partner for the purchase of land and building houses, so that the proportion of profits refers to capital based on a balance (2) Mudharabah financing in sharia banking products is a cooperation partner between the Muamalat Islamic Bank and the fund manager (mudharib), namely the Bank prepares capital for the manager (mudharib) to to finance a business/project in which the profits from the said business are divided based on an agreement between the Bank as shahibul mal and the manager as mudharib; Meanwhile, Musyarakah Syirkatul Milk financing is partnership financing in a partnership to buy goods/assets in the form of house ownership between the bank and its customers/partners who each prepare capital. (3) Legal construction of aqad/murabah financing contract and Musyarakah Syirkatul Milk in the Islamic banking system. 'ah refers to the Fatwa of the National Sharia Council of the Indonesian Ulema Council which is then explained through the sharia principles contained in the legislation. Keywords: Mudarabah, Musyarakah Syirkatul Milk and Bank MuamalatThis study is to analyze the focus of the problem on the application of operational principles, implementation of basic concepts, and legal construction in the contract/mudharabah financing contract and musharakah syirkatul milk in the sharia banking system. So that it can be seen whether the application of the two contracts above is applied in accordance with its provisions. This study uses qualitative methods with normative and empirical juridical research types and is descriptive in nature which describes the applicable laws and regulations which are then linked to legal theories in the implementation of mudharabah and musyarakah syirkatul milk financing. The results of the research are from (1) The application of the operating principle of profit sharing in mudharabah financing refers to the agreement between the Bank as shahibul maal and the manager (mudharib) while Musyarakah syirkatul milk financing, namely the bank unionizes with the customer/partner for the purchase of land and building houses, so that the proportion of profits refers to capital based on a balance (2) Mudharabah financing in sharia banking products is a cooperation partner between the Muamalat Islamic Bank and the fund manager (mudharib), namely the Bank prepares capital for the manager (mudharib) to to finance a business/project in which the profits from the said business are divided based on an agreement between the Bank as shahibul mal and the manager as mudharib; Meanwhile, Musyarakah Syirkatul Milk financing is partnership financing in a partnership to buy goods/assets in the form of house ownership between the bank and its customers/partners who each prepare capital. (3) Legal construction of aqad/murabah financing contract and Musyarakah Syirkatul Milk in the Islamic banking system. 'ah refers to the Fatwa of the National Sharia Council of the Indonesian Ulema Council which is then explained through the sharia principles contained in the legislation. Keywords: Mudarabah, Musyarakah Syirkatul Milk and Bank Muamalat